PENGAMBILALIHAN KREDIT OLEH KARYAWAN ALIH DAYA (OUTSOURCING) PT BANK MANDIRI YANG BERAKIBAT PADA TINDAK PIDANA PENIPUAN - Lilik Septriyana (Faculty of Law, Universitas Lampung, 2020)
The number of frauds has evolved with various forms, such fraud committed by bank employees. This study will focus on three legal issues, namely what is the mechanism for offering credit takeovers to customers at Bank Mandiri which in fact can be carried out by outsourcing personnel? What is the ratio legis for the Decision of PN Tanjungkarang Number 664/Pid.B/2017/PN.Tjk actions of outsourcing employees at PT Bank Mandiri? And how to build a security management system for Bank Mandiri against fraudulent attempts by outsourced employees? The research approach in this study is normative juridical approach and an empirical approach by using secondary data and primary data, and qualitative data analysis.The results of the study is the factors of outsourcing employees of PT Bank Mandiri has authorized to offer credit take over to customers, because of social strata factor, economic factors and environmental factors. Judges' consideration of fraud by outsourced employees of PT Bank Mandiri in Decision Number 664/Pid.B/2017/PN.Tjk is based on evidence, witness statements, expert statements, indictments of the Public Prosecutor, elements of the Prosecutor's Indictment, as well as incriminating and mitigating matters. Ideal law enforcement against fraud by outsourced employees PT Bank Mandiri has the aim to punish outsourced employees so that they become a deterrent and not to repeat their actions later on and tend to improve the lives of many people.